A new zwitterionic electrochromatographic stationary phase based on poly(3‐chloro‐2‐hydroxypropyl methacrylate‐co‐ethylene dimethacrylate) reactive monolith. (17th June 2014) - Aydoğan, Cemil; Çelebi, Bekir; Bayraktar, Aslhan; Ylmaz, Fatma; Denizli, Adil; Tuncel, Ali
<x xml:space="preserve">Abstract</x> A new reactive monolith, poly(3‐chloro‐2‐hydroxypropyl methacrylate‐co‐ethylene dimethacrylate), poly(HPMA‐Cl‐co‐EDMA) was synthesized and post‐functionalized by taurine (2‐aminoethane sulfonic acid) to obtain a zwitterionic stationary phase for capillary electrochromatography. The new stationary phase contained charged groups such as secondary amine providing anodic electroosmotic flow and sulfonic acid groups providing cathodic electroosmotic flow. Hence, the capillary electrochromatography separations with the new zwitterionic monolith were performed with either anodic or cathodic electroosmotic flow. The electrochromatographic separation of alkylbenzenes and phenols was successfully performed. The zwitterionic monolith also allowed the separation of nucleosides using only electrokinetic mode. Theoretical plate numbers up to 105 plates/m were achieved. Our study is the first report based on poly(HPMA‐Cl‐co‐EDMA) reactive monolith post‐functionalized with a zwitterionic ligand allowing to operate in both anodic and cathodic electroosmotic flow modes. Copyright © 2014 John Wiley & Sons, Ltd.